Known and missing left ventricular ejection fraction and survival in patients with heart failure: a MAGGIC meta‐analysis report. (November 2013) - Poppe, Katrina K.; Squire, Iain B.; Whalley, Gillian A.; Køber, Lars; McAlister, Finlay A.; McMurray, John J.V.; Pocock, Stuart; Earle, Nikki J.; Berry, Colin; Doughty, Robert N.; ,
<x xml:space="preserve">Abstract</x> Aims Treatment of patients with heart failure (HF) relies on measurement of LVEF. However, the extent to which EF is recorded varies markedly. We sought to characterize the patient group that is missing a measure of EF, and to explore the association between missing EF and outcome. Methods and results Individual data on 30 445 patients from 28 observational studies in the Meta‐Analysis Global Group in Chronic Heart Failure (MAGGIC) project were used to compare the prevalence of co‐morbidities and outcome across three groups of HF patients: those with missing EF (HF‐mEF), reduced EF (HF‐REF), and preserved EF (HF‐PEF). A total of 29% had HF‐mEF, 52% HF‐REF, and 19% HF‐PEF. Compared with patients in whom EF was known, patients with HF‐mEF were older, had a greater prevalence of COPD and previous stroke, and were smokers. Patients with HF‐mEF were less likely to receive evidence‐based treatment than those with HF‐REF. Adjusted mortality in HF‐mEF was similar to that in HF‐REF and greater than that in HF‐PEF at 3 years [HF‐REF, hazard ratio (HR) 1.03, 95% confidence interval (CI) 0.95–1.12); HF‐PEF, HR 0.78, 95% CI 0.71–0.86]. Conclusion Missing EF is common. The short‐ and long‐term outcome of patients with HF‐mEF is poor and they exhibit different co‐morbidity profiles and treatment patterns compared with patients with known EF. HF patients with missing EF represent a high risk group.